Barriers and enablers for the adoption of professional management - El Gallad, Ahmed (Cranfield University, 2018)
The inability to survive across generations is the main challenge facing all family businesses with only 30% of family firms managing to survive to the second generation, and less than 15% last to the third generation. The generational succession process, primarily from the founder to the second generation accentuates managerial transition, making the founder's style of management potentially no longer the ideal way to run the family firm. It has been argued that the inability of family businesses to adapt to the managerial changes after the founder's era is one of the reasons behind the low survival rate. Professional management is the style of management that follows the founder era and is sought to be applied by the subsequent generations. Therefore, this research investigates the barriers and enablers that family- controlled firms face when they attempt to adopt professional management. Based on the systematic literature review and the empirical study using semi- structured interviews in the Egyptian family business context, the research developed a model that clarifies the three processes involved to adopt professional management during generational transition. The first part of the model provides a deeper understanding of family businesses management through providing clearer demarcations between the family, entrepreneurial and founder management. This helps in clarifying some vagueness and confusion existing in literature between these styles of management. The second part of the model deals with the components of the professional management which are divided between practices and norms. The third part, based on the empirical project, is concerned with the barriers and enablers of professional management where obedience vs. disobedience to the father is considered an enabler or a barrier to professional management. This is the first research that highlights the importance of the relationship between professional management and the father and son relationship in certain Middle Eastern context, which the Egyptian family business context.
Keywords: Family business; professional management; entrepreneurial management; founder management; succession; founding-generation; second generation; Egypt